Exploring the impact of big data analytics capabilities on business model innovation: The mediating role of entrepreneurial orientation - Ciampi, Francesco; Demi, Stefano; Magrini, Alessandro; Marzi, Giacomo; Papa, Armando (Journal of business research, 2021)
Big Data Analytics Capabilities (BDAC) represent critical tools for business competitiveness in highly dynamic markets. In this connection, by leveraging on the Dynamic Capabilities View (DCV) this study analyses the relationship between BDAC and Business Model Innovation (BMI). It argues that the impact of BDAC (a lower-order dynamic capability) on BMI is mediated by Entrepreneurial Orientation (EO; a higher-order dynamic capability). The proposed model is assessed by PLS-SEM (symmetric) and fuzzy-set Qualitative Comparative Analysis (asymmetric) methods using survey data from 253 UK firms. Our findings demonstrate that BDAC have both direct and indirect positive effects on BMI, with the latter being mediated by EO. These results enrich the innovation management literature on Big Data (BD) by showing that BDAC influence company strategic logics and objectives, rather than depending on them, thus playing a significant role in creating value for companies and their stakeholders.